‘A constant black cloud’: the emotional impact of informal caregiving for someone with a lower-grade glioma: research article - Rimmer, Ben; Balla, Michelle; Dutton, Lizzie; Lewis, Joanne; Burns, Richéal; Gallagher, Pamela; Williams, Sophie; Araújo-Soares, Vera; Finch, Tracy; Sharp, Linda (Qualitative health research, 2024)
Those closest to people with lower-grade gliomas (LGGs) often assume the role of informal caregiver (IC). The additional responsibilities mean ICs of people with cancer can experience adverse impacts on their own lives. We explored the emotional impact of informal caregiving for people with LGGs. This was a descriptive qualitative study within the multi-method Ways Ahead project. We conducted semi-structured interviews with individuals from the United Kingdom, who currently, or in the past 5 years, informally cared for someone with an LGG. Interviews encompassed experiences of emotional impact as a consequence of caregiving for someone with an LGG. Inductive thematic analysis was undertaken. We interviewed 19 ICs (mean age 54.6 years; 14 females, 5 males). Participants reported substantial emotional impact. Four themes and associated subthemes were generated: Emotional responses to the illness (e.g. feeling helpless), Emotional responses to the unknown (e.g. anxiety about future uncertainty), Emotional consequences of care recipient changes (e.g. challenges of changed relationship dynamics), and Emotional weight of the responsibility (e.g. feeling burnout). Emotional impact in one area often exacerbated impact in another (e.g. future uncertainty impacted feelings of helplessness). Participants detailed the factors that helped them manage the emotional impact (e.g. being resilient). ICs of people with LGGs can experience wide-ranging emotional responses to and impacts of the illness, uncertain prognosis, care recipient changes, and the toll of caregiving. Adjustment and resilience are key protective factors, though further consideration of ways to identify and fulfil the emotional support needs of ICs of people with LGGs is required.